1994
DOI: 10.1038/eye.1994.94
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous bilateral trabeculectomy

Abstract: In a retrospective study, 24 patients who had undergone simultaneous bilateral trabeculectomy over a 6-year period were reviewed. The duration of disease was at least 2 years, indicating that surgery was not performed as a primary procedure. No patients suffered complications leading to bilateral blindness, although 6 (25%) patients had reduced vision in both eyes at the first postoperative visit, with 3 (13%) worse than 6/36 binocularly. There was no evidence of an asymmetric response in the fall in intraocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
2

Year Published

1995
1995
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
4
2
Order By: Relevance
“…Our results are in agreement with those of Hugkulstone et al. who reported symmetrical reduction of IOP following bilateral trabeculectomy 9 , and Mietz et al. who also found that primary trabeculectomies performed in both eyes of patients have a remarkably similar clinical course but that the second operated eye has a greater risk of Tenon's capsule cyst formation 12 .…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Our results are in agreement with those of Hugkulstone et al. who reported symmetrical reduction of IOP following bilateral trabeculectomy 9 , and Mietz et al. who also found that primary trabeculectomies performed in both eyes of patients have a remarkably similar clinical course but that the second operated eye has a greater risk of Tenon's capsule cyst formation 12 .…”
Section: Discussioncontrasting
confidence: 51%
“…In a study on simultaneous bilateral trabeculectomy, Hugkulstone et al. reported no difference in the outcome between the paired operated eyes 9 ; however, in both of these studies adjunctive antifibrotic therapy had not been used with the filtering surgery.…”
Section: Introductioncontrasting
confidence: 47%
See 1 more Smart Citation
“…A previous report from our unit has shown that there is no significant asymmetry between lOPs recorded from right and left eyes of individuals undergoing surgery to both eyes at the 12 o'clock position. 19 It is therefore unlikely that our surgical bias where all but two right eyes had temporal surgery was influential. Unlike Sanders et at.…”
Section: Discussionmentioning
confidence: 99%
“…The reluctance of ophthalmologists to perform SBIS has been mainly attributable to concerns about bilateral catastrophic complications, such as endophthalmitis, expulsive hemorrhage, or retinal detachment. [3][4][5][6][7][8][9][10][11][12][13][14][15][16] SBIS has been performed in tens of thousands of adult patients, 2,17 with rare reports of bilateral complications. 4,[18][19][20][21][22][23][24][25] There are few reports of SBIS in children in the literature, with a total of 163 cases of bilateral cataract surgeries in children up to 19 years of age and a similar number of cases of bilateral congenital glaucoma surgery (either goniotomy or primary combined trabeculotomy/trabeculectomy).…”
mentioning
confidence: 99%